Towards becoming centres of excellence: Prospects and challenges for malaysian universities. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
In Malaysia, the original blueprint for the setting up of research universities was proposed by the Education Ministry through the National.